Peningkatan Kesensitifan Sensor Al(III) Optik dengan Menggunakan Manik Terkandung Polimer - Suah, FBM; Ahmad, M; Heng, LY (Univ Kebangsaan Malaysia, 2024)
An optical Al(III) sensor base on reflectance principle has been developed using polymer inclusion membranes (PIMs) beads. The immobilized PIMs beads are consists of poly(vinyl chloride) (PVC), Aliquat 336, dioctyl phthalate (DOP) and eriochrome cyanine R (ECR) reagent. The sensor which was based on immobilized PIMs beads produced higher response compared to sensor based on non-immobilized PIMs beads. The response time of the sensor was 3 min with an optimum pH value of 6.0. This optical Al(III) sensor gave a linear response at the range of 5.56x10(-5) - 3.52x10(-4) molL(-1), with the limit of detection value 3.41x10(-5) molL(-1). Validation of Al(III) value in spiked natural water samples by using Al(III) sensor developed in this study showed no significance differences compared with results obtained by using conventional atomic absorption spectrophotometer.